A comparative study of iterative methods for solving first kind Fredholm integral equations with the semi-smooth kernel - Muthuvalu, M.S. (Institute of Electrical and Electronics Engineers Inc., 2016)
The main aim of this paper is to investigate the performance of two iterative methods i.e. Gauss-Seidel (GS) and 2-Point Explicit Group (2-EG) in solving dense linear system associated with the numerical solution of first kind linear Fredholm integral equations. The formulation and implementation of the both methods are presented. In addition, some numerical results are also included to verify the effectiveness of the tested methods. Â© 2015 IEEE.